Risk And Mitigation Analysis of Tidal Flooding Disaster in Medan Belawan Sub-Distric, Medan City - Ngakan Putu Purnaditya; Elfina Rozita; Dwinanti Rika Marthanty (JURUSAN TEKNIK SIPIL, 2021)
Medan Belawan is one of sub-district in Medan City North Sumatera which is the coastal area. The area is particularly vulnerable to coastal hazard that of all people living near coastal line. The most influential of disaster is tidal flood. Tidal flood almost occurs every year with the total inundation area is 26,25 Km2, for example from 2010 until 2017 recorded that the tidal flood inundated around 0,5 m to 2 m in average. There were 98 113 people and 3000-4000 houses, schools, public health facility (puskesmas), highway, fishponds, and international harbor affected. The disaster is not only threatening the community life but also disturbance their sustainable livelihood especially people with low socio-economic condition. This paper provides risk index analysis of the flood and propose the disaster risk reduction measures to reduce the impact of risk. Regarding the analysis, Medan Belawan Sub-district was categorized into high-risk area to the tidal flood, so that its need disaster risk reduction measures. Disaster risk reduction aims to protect affected communities, reduce damage and losses when the disaster happens and make sure sustainable livelihood. Mitigation is one of disaster risk reduction effort that can be divided into structural and non-structural. In structural measure, one of solution is building the impervious seawall which is designed based on increasing of sea level rise due to some factors such as tidal, wave, wind, climate change, land subsidence, and flood which is caused by rainfall with the high intensity. Overall basic design of seawall can build in Medan Belawan Coastal Area is around 4,95 m for its height and will be in residential area that is directly bounded by the sea. In the other hand non-structural approach can be implemented if people permanently live in that area. They can do some adaptation activities to reduce negative impacts and if possible, for taking any advantages of its positive impacts. People can modify their settlements, public facilities and livelihood. Some area in Medan Belawan sub-district also have mangrove forest, there is around 747 hectares. Combination both of approaches aim to reduce the disaster risk.